Chemerin and Prohibitin in the Regulation of Ovarian Follicular Development and their Potential Involvement in Polycystic Ovarian Syndrome - Wang, Qi (Université d'Ottawa / University of Ottawa, 2013)
Follicular growth and maturation are tightly regulated processes, which involve the participation of endocrine, autocrineparacrine factors and intracellular molecules. Due to the numerous research efforts, a large number of regulators and their mechanisms of regulation of follicular growth and differentiation have been established. Although the abnormal expression and activities of some of these regulators are believed to be associated with ovarian dysfunction diseases, such as polycystic ovarian syndrome (PCOS), the etiology and pathogenesis of this syndrome are not completely understood. In this thesis, we have identified two novel regulators of follicular growth and differentiation and examined the cellular and molecular mechanisms that contribute to the folliculogenesis. We present here that chemerin reduces FSH-induced steroidogenic enzyme expression and steroid hormone production in follicles and granulosa cells. Prohibitin expression is upregulated by chemerin and knockdown of prohibitin attenuates the suppressive role of chemerin on steroidogenesis, an action regulated by Akt. Using an androgenized rodent model, we also present the dysregulation of chemerin and prohibitin and their association with dysregulated follicular steroidogenesis. Our data and preliminary clinical studies demonstrate the potential involvement of chemerin and prohibitin in the etiology of PCOS. These studies significantly improve the knowledge of ovarian functions and the pathophysiology of PCOS, and provide important clues for the development of novel diagnosis biomarkers and new treatment strategies for this complex syndrome.
Keywords: Follicular Development; Polycystic Ovarian Syndrome; Steroidogenesis; Chemerin; Prohibitin